Papillary renal neoplasm with reverse polarity: a case report and literature review - Gonzalez, Diego; Kokoneshi, Kris; Kwon, Sam; Mathews, Ryan Thomas; Antar, Ryan Michael; Ali, Maher; Kassa, Abiye; Whalen, Michael (Frontiers in Oncology, 2025)
IntroductionPapillary renal neoplasm with reverse polarity (PRNRP) is a rare subtype of papillary renal cell carcinoma (RCC) with unique morphology, molecular features, and good prognosis. Given its rarity, with less than 100 reported cases, further characterization is needed to enhance diagnostic accuracy and inform management strategies.Case presentationWe report the case of a 59-year-old African American female with an incidentally discovered 2.1 cm left renal mass on imaging. The patient has a medical history of hypertension, asthma, hyperlipidemia, vertigo, depression/anxiety, and prediabetes. Further evaluation via contrast-enhanced CT confirmed an enhancing renal mass without evidence of metastasis. She underwent a robotic-assisted partial nephrectomy, and postoperative pathology confirmed PRNRP with pT1aNxMxR0 staging and ISUP nuclear grade 1. Immunohistochemical analysis demonstrated positive staining for GATA3, CK7, and EMA, and Vimentin and negative for AMACR and CA IX. Molecular profiling revealed a KRAS mutation, a key feature of PRNRP. Postoperative recovery was uneventful aside from transient vertigo, and no further treatment was required.ConclusionThis case reinforces the distinct morphological and molecular profile of PRNRP, distinguishing it from other papillary RCC subtypes. The indolent behavior, absence of metastatic cases, and characteristic molecular profiling and immunohistochemical markers highlight the importance of accurate classification for optimal patient management. Furthermore, the PD-L1 positivity observed in this case raises potential implications for immune checkpoint therapy, an area warranting further investigation. As PRNRP is recently classified, continued study is essential to refine diagnostic, therapeutic, and surveillance strategies for this rare renal neoplasm.